Game of Thrones Sebagai Arsitektur Ekonomi Politik Global Versi Indonesia - Dien Yudithadewi; Bonifasius Santiko Parikesit; Eka Wenats Wuryanta (Sospol : Jurnal Sosial Politik, 2020)
Abstract As part of the political communication channel, speech is an essential tool to convey messages, especially at the global political scope. In a speech at the IMF-World Bank 2018 meeting, President Joko Widodo used the phrase 'winter is coming' from the story of the popular television series Game of Thrones as a presupposition of the global political economy situation. Based on President Jokowi's speech, this paper aims to understand the changes in the international political architecture caused by the spirit of economic liberalism from developed countries. The study applied the discourse analysis approach of Norman Fairclough's version. Referring to Fairclough, presuppositions are the key to understanding how reality is differentiated and presented. In examining the contents of the speech, the author will choose words/sentences that lexically relate to Game of Thrones or the context of de-globalization through the phenomenon of protectionism and trade war. The speech represents an attempt to protest from developing countries to the superpower countries. President Jokowi reminded superpower countries that the protectionism and trade wars will only lead to de-globalization. Instead of competing for power domination, Indonesia is calling for the idea of an equilibrium hegemony in the political economy to all member-states.